فعالية رأس مال المخاطر في تمويل المؤسسات الناشئة بالجزائر - أشرف الدين خلايفية; بشرى بن رجم (My University, 2021)
The increasing trend towards integration into a unified global economy has led countries to empower the emerging and small enterprises sector within their development priorities and strategies, but the latter faces many problems and obstacles, as funding takes the largest share of them. It is small and therefore will not fulfill the role entrusted to it due to the limited resources with which it is launched in addition to the difficulty of obtaining loans from banks due to the high cost of borrowing, exaggeration in terms and the request for guarantees in kind. Accordingly, it has become necessary to search for a financing source that has advantages commensurate with the financial needs of these institutions. From this point of view, we will try in this research to study the role and effectiveness of venture capital as a modern technology for financing emerging institutions, by realizing the basic concepts related to this financing technology, and highlighting its importance as an effective financing alternative. ................................................. أدى الاتجاه المتزايد نحو الاندماج في اقتصاد عالمي موحد إلى قيام الدول بتمكين قطاع المشاريع الناشئة والصغيرة ضمن أولوياتها واستراتيجياتها التنموية، إلا أن الأخيرة تواجه العديد من المشاكل والعقبات، حيث يأخذ التمويل النصيب الأكبر منها. وهي صغيرة وبالتالي لن تقوم بالدور المنوط بها نظرا لمحدودية الموارد التي تنطلق بها بالإضافة إلى صعوبة الحصول على القروض من البنوك بسبب ارتفاع تكلفة الاقتراض والمبالغة في الشروط وطلب الضمانات في عطوف. وعليه، أصبح من الضروري البحث عن مصدر تمويل يتمتع بمزايا تتناسب مع الاحتياجات المالية لهذه المؤسسات. ومن هذا المنطلق سنحاول في هذا البحث دراسة دور وفعالية رأس المال الاستثماري كتقنية حديثة لتمويل المؤسسات الناشئة، من خلال إدراك المفاهيم الأساسية المتعلقة بهذه التقنية التمويلية، وإبراز أهميتها كبديل تمويلي فعال. .